2002
DOI: 10.1191/0961203302lu203ra
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydroxychloroquine in systemic lupus erythematosus. Prospective long-term study of an Israeli cohort{

Abstract: Systemic lupus erythematosus-associated irreversible organ/system damage was previously associated with various clinical and demographic features. We analysed the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SLICC/ACR DI) in a cohort of 151 Israeli patients followed for a mean (+/- s.d.) period of 45.7 +/- 37.4 months. Mean score of SLICC/ACR DI at the first and last encounters were 0.17 +/- 64 and 1.64 +/- 2.1, respectively (P < 0.0001). Multiple logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 34 publications
(42 reference statements)
4
75
0
15
Order By: Relevance
“…The use of hydroxychloroquine has been shown to have cardioprotective effect as it has suggested that it has antiatherogenic effects [16,17]. Generally, the treatment for myocardial infarction, pulmonary hypertension and valvular disease are similar as those without APLS.…”
Section: Short Communicationmentioning
confidence: 99%
“…The use of hydroxychloroquine has been shown to have cardioprotective effect as it has suggested that it has antiatherogenic effects [16,17]. Generally, the treatment for myocardial infarction, pulmonary hypertension and valvular disease are similar as those without APLS.…”
Section: Short Communicationmentioning
confidence: 99%
“…Активность болезни и выраженность обострения во время проведения исследования также предшествовали нара-станию степени повреждения в гонконгской когорте [32]. Прямая связь между высокой активностью и развитием по-вреждений выявлена и в других исследованиях [21,41].…”
Section: и н д е к с п о в р е ж д е н и я S L I C C ( S Y S T E M I unclassified
“…They also reduce mortality 12-14 and the number of flare-ups 15 as well as limit damage to various organs. 16,17 Metabolic benefits of HCQ and CQ are presented in TAbLE 1. They have an antiaggregatory effect, particularly in SLE associated with antiphospholipid syndrome, 11 and hypolipemic effect.…”
Section: Review Articlementioning
confidence: 99%